Significant change in micro mechanical, structural and electrical properties of MgB2 superconducting ceramics depending on argon ambient pressure and annealing duration - Ozturk, O.; Asikuzun, E.; Kaya, S. (Springer Science and Business Media LLC, 2015)
In this study, the effects of different Ar pressure (vacuum, 0, 10 and 20 bar) and different annealing times (0.5 and 1 h) on microstructural, mechanical and superconducting properties of the bulk superconducting MgB2 are investigated. The samples are produced using the solid state reaction method. X-ray diffraction and scanning electron microscopy measurements are performed for phase formation, crystal structure, lattice parameters, particle size analysis, grain orientations, grain connectivity, and surface morphology of MgB2 samples. The superconducting properties are studied by dc resistivity measurements. In this study we have focused on microhardness measurements to investigate the mechanical properties. Vickers microhardness test is employed for determination of mechanical properties of the samples. The experimental microhardness results are analyzed by Meyer’s law, proportional sample resistance model, elastic–plastic deformation model, Hays Kendall (HK) approach, and indentation induced cracking (IIC) model. HK approach is identified as the most appropriate model for MgB2 superconducting samples exhibiting the indentation size effect behavior; for the other samples that have reverse indentation size effect behavior IIC model is appointed as the most appropriate model.